GROWTH AND MINERAL NUTRITION IN SEEDLINGS OF JACARANDÁ-DA-BAHIA SUBJECTED TO NUTRIENT DEPRIVATION - Carlos, Leandro; Venturin, Nelson; Farias, Elias de Sá; Venturin, Regis Pereira; Macedo, Renato Luiz Grisi (Floresta, 2014)
Abstract With the objective of evaluating the nutritional requirements and the effects of nutrient deprivation in developing of Jacarandá da Bahia seedlings (Dalbergia nigra (Vellozo) Freire Allemao ex Bentham), a greenhouse experiment was conducted. The experiment had fully randomized design, with 12 treatments and 8 replications. The following treatments were applied: Complete 1 (C1-fertilized with N, P, K, S, B, Cu, Zn and liming as Ca and Mg sources), complete 2 (Complete 1 – liming with CaSO4.2H2O and MgSO4.7H2O as Ca and Mg sources), C1-N, C1-P, C1-K, C1-S, C1-B, C1-Zn, C1-liming, C2-Ca, C2-Mg and control. Diameter and height were measured and plants were separated into aerial part and root system. Samples were dried, weighed and levels of nutrients in the aerial dry matter were measured. Phosphorus was the most growth limiting factor, the sequence of nutritional requirements presented by Jacarandá da Bahia seedlings in relation to the complete treatment was: P > Ca > B > K > S > Zn > Mg > N. Keywords: Missing element; Dalbergia nigra; rainforest; hardwood. Resumo Crescimento e nutrição mineral de mudas de jacarandá-da-bahia sob efeito da omissão de nutrientes. Com o objetivo de avaliar exigências nutricionais e os efeitos da omissão de nutrientes no desenvolvimento de mudas de Jacarandá da Bahia (Dalbergia nigra (Vellozo) Freire Allemao ex Bentham), conduziu-se um experimento com o uso da técnica de elemento faltante. Foram empregados 12 tratamentos, em um delineamento inteiramente casualizado com oito repetições. Adotaram-se os seguintes tratamentos: Completo 1 (adubado com N, P, K, S, B, Cu, Zn e calagem como fonte de Ca e Mg e corrigindo acidez do solo), completo 2 (completo 1 – calagem tendo CaSO4.2H2O e MgSO4.7H2O como fontes de Ca e Mg sem corrigir acidez do solo), C1-N, C1-P, C1-K, C1-S, C1-B, C1-Zn, C1-calagem, C2-Ca, C2-Mg e testemunha. Foram medidos diâmetro e altura das plantas e separadas em parte aérea e sistema radicular. As mudas foram secas, pesadas e foram determinados os teores de nutrientes na matéria seca da parte aérea. O fósforo foi o nutriente mais limitante ao crescimento de jacarandá da Bahia; a sequência de exigência nutricional apresentada pelas mudas de Jacarandá da Bahia em relação ao tratamento completo em ordem decrescente foi: P > Ca > B > K > S > Zn > Mg > N. Palavras-chave: Elemento faltante; Dalbergia nigra; Mata Atlântica; Madeira nobre.